Comparative assessment of Industrial air pollutant exposure on pulmonary function and respiratory symptoms among primary school children, Kala Amb, Sirmour, Himachal Pradesh, India - Kashyap, Rashmi; Barall, Deepesh; Mazta, Saligram (International Journal of Research in Medical Sciences, 2020)
Background: Outdoor air quality has been connected with the prevalence of allergic respiratory infections in children. The impact of industrial pollution on respiratory health during early years of life in school children is a major concern. Pulmonary function tests can be used to assess the impact of air pollution and the degree of airway reactivity. Methods: A cross sectional comparative study was conducted between Primary school children aged 6 to 10 years in the industrial area and non-industrial area. Structured questionnaire based data was recorded from the students regarding respiratory symptoms. Spirometric parameters recorded were Forced Vital Capacity (FVC), Forced Expiratory Volume at one second (FEV1), Maximal Midexpiratory flow (FEF 25-75%) and Peak Expiratory Flow Rate (PEFR). Results: Data from 102 students from each of the two primary schools revealed mean forced expiratory volume in 1 second (FEV1) as 1.01±0.31 L/sec in industrial area and 1.12±0.34 L/sec in non-industrial area (p=0.01). Four or more episodes of allergic rhinitis in the last year were present in 24/84 (28.5%) children in the industrial area as compared to 8/90 (8.8%) in the non-industrial area (p=0.002). Point prevalence of allergic rhinitis was 36 (35.3%) students in industrial area and 22 (21.6%) students in non-industrial area (p=0.03). Conclusions: Industrial air pollution has impact on the lung function tests of school children in the age group of 6 to 10 years with significant difference in spirometric parameters of FEV1, frequency of episodes of allergic rhinitis and point prevalence of allergic rhinitis.